The Effect of Financial Ratio on Stock Prices of Companies Listed on the Indonesia Stock Exchange - Ahmad Ainul Yaqin; Habsyah Fitri; Siti Khomsatun (Innovation Business Management and Accounting Journal, 2024)
This study aims to analyze and determine the effect of Current Ratio, Debt to Equity Ratio, Net Profit Margin, Earning Per Share, and Return on Asset on the Share Price of companies listed on the Indonesia Stock Exchange in 2017-2021. This research uses the hypothesis testing method, namely the associative hypothesis method. This research uses research data, namely the company's annual financial report obtained from the idx.co.id website and the website of each company. This study used a sample of food and beverage subsector companies listed on the Indonesia Stock Exchange in 2017-2021. In the selection of samples using the Purposive Sampling technique so that 12 companies were produced that could be used as samples in this study. This study is for data analysis using multiple linear regression. This study used independent variables including Current Ratio, Debt to Equity Ratio, Net Profit Margin, Earning Per Share, Return on Asset. The Dependent variable used in this study is the closing share price. The results of this study show that the Current Ratio, Debt to Equity Ratio, Net Profit Margin, Earning Per Share and Return on Asset have a joint effect on the share price of companies listed on the Indonesia Stock Exchange in 2017-2021. The results of the study partially stated that the Debt to Equity Ratio and Net Profit Margin affect the stock price, while the Current Ratio, Earning Per Share, and Return on Asset do not affect the share price of companies listed on the Indonesia Stock Exchange in 2017-2021.